2014
DOI: 10.1144/jgs2013-135
|View full text |Cite
|
Sign up to set email alerts
|

Flip-flop detachment tectonics at nascent passive margins in SE Afar

Abstract: Abstract:We propose a two-stage tectonic evolution of SE Afar in Djibouti leading to the complex development of highly asymmetric conjugate margins. From c. 8.5 to c. 2 Ma, an early mafic crust developed, associated in the upper crust with synmagmatic growth faults dipping dominantly to the SW. After an erosional stage, a new detachment fault system developed from c. 2 Ma with an opposite sense of motion (i.e. to the NE), during an amagmatic extensional event. In the Asal area, break-up occurred after c. 0.8 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Between the MI and AG active rift segments, the Mak'Arrassou transfer zone has been recognized as an oblique transfer zone with tectonic features consistent with the northwestern propagation of the AR (Tapponnier & Varet 1974;Manighetti et al 2001), when Le Gall et al (2011) and Geoffroy et al (2014) identify this region as a large monoclinal flexure, similar to those observed along the volcanic passive margin. Due to this spatial configuration of the GPS velocity field and in particular the lack of velocity vector northeast of the Mak'Arrassou, the strain rate tensor inversion shows that NEtrending extension occurs at the southern part of the Mak'Arrassou region, with a low counter-clockwise rotation rate (∼2.4 • /Myr) in agreement with low palaeomagnetic values (Manighetti et al 2001).…”
Section: The Aden Propagatormentioning
confidence: 85%
“…Between the MI and AG active rift segments, the Mak'Arrassou transfer zone has been recognized as an oblique transfer zone with tectonic features consistent with the northwestern propagation of the AR (Tapponnier & Varet 1974;Manighetti et al 2001), when Le Gall et al (2011) and Geoffroy et al (2014) identify this region as a large monoclinal flexure, similar to those observed along the volcanic passive margin. Due to this spatial configuration of the GPS velocity field and in particular the lack of velocity vector northeast of the Mak'Arrassou, the strain rate tensor inversion shows that NEtrending extension occurs at the southern part of the Mak'Arrassou region, with a low counter-clockwise rotation rate (∼2.4 • /Myr) in agreement with low palaeomagnetic values (Manighetti et al 2001).…”
Section: The Aden Propagatormentioning
confidence: 85%
“…A number of authors have suggested faults exist within highly magmatic settings. An asymmetric detachment fault has been observed in the Afar region, where two stages of extension over listric faults are inferred to have caused faulted rollover anticlines [ Geoffroy et al ., ]. This differs from our prediction of SDR evolution, where we propose the crust was thinned in just one stage.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, from a chronological point of view, the crust is “rethickened” after an extension phase. This may appear to be at odds with observations made at other onshore volcanic passive margins, such as the SE Afar rift in Djibouti [ Geoffroy et al ., ]. Here syn‐tectonic prisms of 8 to 2 Ma age (stage partly intermediate between Figures b and c) are thought to be controlled by rollover faults that are rooted in a detachment at depth that controls the location of future breakup.…”
Section: Discussionmentioning
confidence: 99%
“…Seismic studies show the presence of a broad mantle anomaly rooted at the core‐mantle boundary [ Ritsema and Allen , ; Simmons et al ., ; Bastow et al ., ; Li et al ., ; Ritsema et al ., ], and the Afar rift is therefore considered an example of rifting following impingement of a plume‐like thermal anomaly. The Afar rift system (Figure ) has been interpreted as an asymmetric rift, analogous to SDR, where strain and magmatism have migrated toward the rift center and play a major role in dyking [ Ebinger and Casey , ; Wolfenden et al ., ], or alternatively, as a detachment‐dominated rift [ Ghebreab and Talbot , ; Geoffroy et al ., ]. The relationship between normal faulting, dyking, and low‐angle faults therefore remains unclear.…”
Section: Introductionmentioning
confidence: 99%